Active noise control in duct with a harmonic acoustic pneumatic source. (May 2021) - Drant, Julien; Micheau, Philippe; Berry, Alain
Highlights: Acoustic pneumatic sources provide a solution for active noise control applications. The source used is a mechanical parametric modulator piloted in amplitude and phase. Duct inside and outside pressure minimization brings radiated noise attenuation. Attenuations performances higher than 20 dB are obtained over up to 800 Hz. Abstract: Electrodynamic loudspeakers usually used in active noise cancellation show several limitations due to the difficulty of embedding in complex harsh conditions, e.g. the conditions for active noise control of tonal turbofan noise. Instead, this study presents a Harmonic Acoustic Pneumatic Source (HAPS), designed to generate a controlled harmonic anti-noise from a pneumatic source. It is based on a controlled flow valve and a controlled flow chopper, creating a variable orifice to generate a harmonic anti-noise whose magnitude is related to the flow valve opening and whose phase is related to the angular position of the flow chopper. Such original HAPS device is driven with a dedicated complex envelope controller, since the chopper is controlled by a phase-locked loop. An experimental set-up is used to evaluate the precision of the HAPS in a plane wave active cancellation scheme with in-duct or external error microphones and a loudspeaker generating a primary sound pressure level up to 155 dB in the duct. The experimental results show that the HAPS is sufficiently stable and accurate to achieve single-frequency sound pressure level attenuations over 20 dB from 500 Hz to 800 Hz.